2011
DOI: 10.1021/jp110398j
|View full text |Cite
|
Sign up to set email alerts
|

HCl Adsorption and Ionization on Amorphous and Crystalline H2O Films below 50 K

Abstract: Molecular beams were used to grow amorphous and crystalline H(2)O films and to dose HCl upon their surface. The adsorption state of HCl on the ice films was probed with infrared spectroscopy. A Zundel continuum is clearly observed for exposures up to the saturation HCl coverage on ice upon which features centered near 2530, 2120, 1760, and 1220 cm(-1) are superimposed. The band centered near 2530 cm(-1) is observed only when the HCl adlayer is in direct contact with amorphous solid water or crystalline ice fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 54 publications
4
43
0
Order By: Relevance
“…They find a 43 kJ/mol binding energy, similar to what is reported by Olanrewaju et al (2011), plus an additional 21 kJ/mol if one includes the free energy of the ionization, which corresponds to the solvation process, that is, the proton transfer of the hydronium ion to the water matrix (for crystalline ice). Ayotte et al (2011) find a sticking coefficient of unity below 60 K, indicating that the adsorption process is highly efficient in typical molecular cloud environments. Depending on the degree of ordering of the halogens in the water ice matrix, one can equivalently describe this configuration in terms of water complexes of the form H 2 O·HCl (formation of hydrates as discussed by Delzeit et al 1993) which decay as temperature goes up, in a process reminiscent of hydrated minerals (similar to hydrated halite).…”
Section: Comet Grain Modelmentioning
confidence: 88%
See 1 more Smart Citation
“…They find a 43 kJ/mol binding energy, similar to what is reported by Olanrewaju et al (2011), plus an additional 21 kJ/mol if one includes the free energy of the ionization, which corresponds to the solvation process, that is, the proton transfer of the hydronium ion to the water matrix (for crystalline ice). Ayotte et al (2011) find a sticking coefficient of unity below 60 K, indicating that the adsorption process is highly efficient in typical molecular cloud environments. Depending on the degree of ordering of the halogens in the water ice matrix, one can equivalently describe this configuration in terms of water complexes of the form H 2 O·HCl (formation of hydrates as discussed by Delzeit et al 1993) which decay as temperature goes up, in a process reminiscent of hydrated minerals (similar to hydrated halite).…”
Section: Comet Grain Modelmentioning
confidence: 88%
“…At low temperatures and low concentrations, there is a significant free energy associated with the adsorption of hydrogen halides (sub-monolayer coverage) onto water ice. The uptake and autoionization of HCl on low temperature water ice has been studied experimentally (Ayotte et al 2011;Olanrewaju et al 2011;Parent & Laffon 2005;Park & Kang 2005) for porous amorphous, amorphous, and crystalline water ice surfaces. The process can be interpreted as rapid ionization of HCl at the surface at temperatures as low as 20 K. The surface of the ice becomes disordered as HCl autoionizes and forms contact ion pairs (Olanrewaju et al 2011).…”
Section: Comet Grain Modelmentioning
confidence: 99%
“…Theoretical studies suggest this process is energetically allowed on an ice surface and proceeds rapidly by tunnelling at 190 K (Robertson & Clary 1995). Experimental studies show that HCl adsorbs dissociatively at sub-monolayer coverages onto the surface of dense amorphous solid water at temperatures as low as 20 K (Ayotte et al 2011). As dangling OH bonds are involvedwhich will be omnipresent on growing interstellar ice surfacesand in view of the long interstellar timescales, we consider solvation likely on a 10 K icy interstellar grain.…”
Section: Depletion Of Chlorinementioning
confidence: 99%
“…For example, our recent theoretical study demonstrated [24] how successive aggregation of four water molecules can explain the HCl dissociation observed under the cryogenic conditions of a superfluid helium droplet in terms of an "aggregation-induced chemical reaction". [27,28] Recent experiments using three complementary techniques, namely, X-ray absorption, photoemission, and infrared spectroscopy, demonstrated [29,30] that HCl dissociation takes place spontaneously, that is, without an energy barrier, upon adsorption on the ice surface, even at temperatures as low as 20 K. Acid dissociation remains in the focus of current research, not only because of its fundamental relevance, but also due to its practical importance. [27,28] Recent experiments using three complementary techniques, namely, X-ray absorption, photoemission, and infrared spectroscopy, demonstrated [29,30] that HCl dissociation takes place spontaneously, that is, without an energy barrier, upon adsorption on the ice surface, even at temperatures as low as 20 K. Acid dissociation remains in the focus of current research, not only because of its fundamental relevance, but also due to its practical importance.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Apart from water clusters, dissociated HCl was studied in other imperfect or heterogeneous solvation environments, such as the liquid water/vapor interface [26] or the surface of water ice. [27,28] Recent experiments using three complementary techniques, namely, X-ray absorption, photoemission, and infrared spectroscopy, demonstrated [29,30] that HCl dissociation takes place spontaneously, that is, without an energy barrier, upon adsorption on the ice surface, even at temperatures as low as 20 K. Acid dissociation remains in the focus of current research, not only because of its fundamental relevance, but also due to its practical importance. HCl dissociation on ice was found to enable formation of chlorine radicals upon subsequent excitation by light, [31] and thus a pos-…”
Section: Introductionmentioning
confidence: 99%